Distorções salariais na administração pública: impactos na motivação dos servidores da Fundação Oswaldo Cruz - Paes, Filipe Carvalho de Alarcão (2017)
Purpose - The objective of the research is to study the possible impacts of remunerationinequalities on the motivational aspects of public workers, focusing on the health managers ofOswaldo Cruz Foundation (FIOCRUZ).Methodology – A bibliographic research was performed, searching for articles and academicstudies that addressed the correlation between remuneration and motivation. We also sought adocumentary analysis, based on a quantitative approach, comparing the remuneration valuesreceived by the various public workers. To conclude we used a field research, applying a surveymodel questionnaire.Findings- The study shows that employees relationships go far beyond simple exchanges basedon material resources; however, workers still perceive positively the influence of rewardsystems and pay on their motivation. And as important as the value of these rewards is the senseof justice perceived by the worker.Research limitations – The activities of the positions belonging to the study sample, althoughsimilar, have different complexities according to the organization in which they are performed.In addition, the results of the study cover only part of management analysts’ reality. Anotherpoint is the variation of the remuneration values received by the different careers in the year2017, data that have not yet been available until the conclusion of this study.Practical implications – This study should contribute to the strengthening of existing literatureon motivation in the public service, pushing new research to seek solutions to the salarydistortions that occurred between different careers in public administration.Social implications - The current society’s demand is for an efficient public service, meetingthe needs of the citizen in the best way and at the lowest possible cost. Public job and salaryplans must be in line with this reality. The presented literature has foundations able to assist thepublic agents in the development of policies directed to the management of people in thegovernmental area.